Text-fig. 11. a, b: Coriaria aff. myrtifolia. a: Oriolo MSF 647. b: Oriolo MSF 704. c, d: Populus aff. alba. c: Oriolo MSF 745. d: Oriolo MSF 725. e: Populus aff. tremula Oriolo MSF 749. f–h: Populus aff. nigra. f: Oriolo MSF 737. g: Oriolo MSF 742. h: Oriolo MSF 738. Scale bars 10 mm (a–d), 50 mm (e–h). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 11. a, b: Coriaria aff. myrtifolia. a: Oriolo MSF 647. b: Oriolo MSF 704. c, d: Populus aff. alba. c: Oriolo MSF 745. d: Oriolo MSF 725. e: Populus aff. tremula Oriolo MSF 749. f–h: Populus aff. nigra. f: Oriolo MSF 737. g: Oriolo MSF 742. h: Oriolo MSF 738. Scale bars 10 mm (a–d), 50 mm (e–h). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 238, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867